PENGARUH OUTDOOR LEARNING BERBASIS INKUIRI TERHADAP HASIL BELAJAR MATERI EKOSISTEM (FMIPA UNNES, 2012)
This research aimed to indentify the effect of the implementation of Inquiry-based Outdoor Learning on students’ learning achievement in Ecosystem at SMP N 2 Selopampang. This study was a Quasi Experimental Design with Pre and Post-test which was applied on the VII A class as a control group and VII B as an experimental group. Sample was collected by a convenience sample technique. Questionaire was used to collect data of inquiry based activity of students in Outdoor Learning. Tests were used to collect data of students’ cognitive learning achievement. Observation sheets were used to record student’s psychomotoric learning achievement, and physchology scale was used to measure students’ affective learning achievement. Data were analysed by quantitative methods. Data were analyzed by t-test and simple linear regression. T-test result showed that there were a significant difference between both groups (tcount > ttable). Linear regression indicated that inquiry based Outdoor Learning brought a significant effect on students’ learning achievement (sig. value <0.05). The conclusion of this research was that implementation of Inquiry-based Outdoor Learning approach had a significant effect on students’ learning achievement. Penelitian ini bertujuan untuk menguji pengaruh Outdoor Learning berbasis inkuiri terhadap hasil belajar siswa pada materi ekosistem di SMP N 2 Selopampang. Penelitian ini merupakan penelitian Quasi Experimental Design dengan pola Pre and Post-test Design yang diterapkan pada kelas VII A sebagai kelas kelompok kontrol dan VII B sebagai kelompok eksperimen. Pengambilan sampel menggunakan teknik convenience sampling. Data aktivitas inkuiri siswa dalam Outdoor Learning dikumpulkan dengan angket yang diisi oleh siswa. Data hasil belajar dalam ranah kognitif siswa dikumpulkan dari tes materi ekosistem, data hasil belajar dalam ranah psikomotorik diperoleh melalui lembar observasi, data hasil belajar dalam ranah afektif tentang peduli lingkungan dikumpulkan dengan skala psikologi siswa. Data dianalisis secara kuantitatif. Data dianalisis dengan uji t dan analisis regresi linier sederhana. Hasil uji t menunjukkan perbedaan yang nyata dari kedua kelompok (thitung>ttabel). Hasil uji regresi linier sederhana mengindikasikan bahwa Outdoor Learning berbasis inkuiri berpengaruh secara nyata pada hasil belajar siswa (nilai sig.<0.05). Simpulan dari penelitian ini adalah penerapan Outdoor Learning berbasis inkuiri berpengaruh signifikan terhadap hasil belajar siswa.